Fiction and Suffering: The World Vision of Young Authors’ Fiction, Post-ISIS Attack, 2014-2017 - Omar, Ameen A. (Humanities Journal of University of Zakho, 2018)
The present study examines Kurdish novels written under particular socio-political conditions post-ISIS attack 2014-2017. The study is an attempt to investigate the degree to which these circumstances influenced young authors' world visions. For this purpose, two novels written by young authors have been chosen as samples for the study: Naxên Derizî (The Cracked Psychologies) by Omêd Segvan in 2015; and Atra (Atra) by Diyar Eredinî in 2017. In order to conduct the present study, it is essential to use a theory which considers socio-political context. Lucien Goldmann’s genetic structuralist approach, which relates literary works to social affairs, has been chosen as a theory for the study. However, the study is concerned only with ‘world view’, a concept which Goldmann set out in his famous book The Hidden God. This book is fundamental to Goldmann's genetic structuralist approach. By applying Goldmann’s theory to the selected novels, the reasons behind the tragic view discernible in the novels of this period in Kurdish history will be apparent.